Synthesis, molecular docking, and biological evaluation of methyl-5-(hydroxyimino)-3-(aryl-substituted)hexanoate derivatives - Gudimani, Parashuram; Shastri, Samundeeswari Lokesh; Pawar, Varsha; Hebbar, Nagashree Uday; Shastri, Lokesh Anand; Joshi, Shrinivas; Vootla, Shyam Kumar; Khanapure, Sheela; Sunagar, Vinay (European Journal of Chemistry, 2022)
Beta-aryl keto hexanoic acids (5a-l) were synthesized efficiently, followed by esterification that afforded beta-aryl keto methylhexanoates (6a-l). The chemo-selective ketoxime beta-aryl methyl hexanoates (7a-l) were isolated in good yields. Spectroscopic methods were used to characterize the obtained moieties. The antioxidant, anti-inflammatory, and antibacterial properties of the effectively synthesized compounds 7a-l were also investigated. The anti-inflammatory activity of the compounds 7c, 7f, 7i, and 7l was excellent, with a low IC50 value at micromolar concentration, which was much better than the reference diclofenac. All synthesized compounds 7a-l were assessed for their in vitro antibacterial activity against S. aureus, B. subtilis and E. coli. Most of the compounds exhibited promising activity against Gram-positive bacterial strain, compound 7i showed excellent activity compared to standard streptomycin and in the case of E. coli, compounds 7b, 7c, 7j, 7k and 7l have shown moderate activity. Further, the cytotoxic activities of the compounds were assessed against lung cancer cells (A549) by using MTT assay. The possible interaction mechanism of the molecules 7c and 7g with Gram-negative strain E. coli DNA gyrase B in complex with PDB ID: 4DUH was studied.